Perjanjian Kerja Waktu Tertentu dalam Hukum Ketenagakerjaan - Rifqy Tombak Matahari; Dimas Pramodya Dwipayana (CV. ITTC INDONESIA, 2025)
A Fixed-Term Employment Agreement (PKWT) is a form of employment relationship specifically regulated by Indonesian labor law. PKWT is used for temporary work as stipulated in the Manpower Law and other regulations. However, in practice, PKWT often raises legal issues, particularly related to abuse by employers to avoid obligations that should be given to permanent workers. The purpose of this study is to examine the legal concept of PKWT and the legal requirements and protections for workers in a fixed-term employment relationship. The method used is a normative approach by examining relevant laws and regulations, legal doctrine, and court decisions. The results of the study indicate that although PKWT has a clear legal basis, its implementation in the field still often violates the principles of justice and protection for workers. Therefore, strict supervision and law enforcement are needed to ensure that the implementation of PKWT does not harm workers.